2004
DOI: 10.1196/annals.1331.020
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Antioxidant Treatment in Diabetes

Abstract: The many studies on oxidative stress, antioxidant treatment, and diabetic complications have shown that oxidative stress is increased and may accelerate the development of complications through the metabolism of excessive glucose and free fatty acids in diabetic and insulin-resistant states. However, the contribution of oxidative stress to diabetic complications may be tissue-specific, especially for microvascular disease that occurs only in diabetic patients but not in individuals with insulin resistance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(128 citation statements)
references
References 67 publications
2
114
0
11
Order By: Relevance
“…In addition, oxidative stress also triggers a series of cellular responses, including the activation of protein kinase C and the transcription factor nuclear factor-B, and so forth. Inappropriate activations of these important regulatory molecules would have deleterious effects on cellular functions, leading to the pathogenesis of various diabetic complications including retinopathy, nephropathy, and neuropathy (4,32,33). Since oxidative stress also contributes to several deleterious changes caused by STZ, antioxidants or NO scavengers substantially attenuate STZ toxicity (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oxidative stress also triggers a series of cellular responses, including the activation of protein kinase C and the transcription factor nuclear factor-B, and so forth. Inappropriate activations of these important regulatory molecules would have deleterious effects on cellular functions, leading to the pathogenesis of various diabetic complications including retinopathy, nephropathy, and neuropathy (4,32,33). Since oxidative stress also contributes to several deleterious changes caused by STZ, antioxidants or NO scavengers substantially attenuate STZ toxicity (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Lipoic acid supplementation completely prevents diabetes-induced increase in nitrotyrosine and activation of NF-B while decreasing the levels of VEGF and oxidatively modified proteins in the rat retina [129]. Apart from lipoic acids other experiments have also been tried in animal models, such as vitamin C and vitamin E. All of them have shown improved biological and pathological changes and prevented or slowed the progression of diabetic complications [130]. The potential benefit of vitamin E has been shown in DR by its free radical scavenger activity outside the cell through nonenzymatic mechanisms [100].…”
Section: Inhibition Of Ros Antioxidants and Hexosamine Pathway As Ementioning
confidence: 99%
“…Finally, subject characteristics such as populations with and without type 2 diabetes could result in differences in how the individual populations respond to vitamin C supplementation. Diabetic patients have greater levels of oxidative stress than other groups of patients at risk of cardiovascular disease 41 and therefore may respond more favorably to vitamin C supplementation. Previous studies using type 2 diabetics has revealed diminished tissue levels and impaired vitamin C recycling mechanisms.…”
Section: Discussionmentioning
confidence: 99%